The Walking Dead at Saqqara Strategies of Social and Religious Interaction in Practice - Weiss, Lara (Religionsgeschichtliche Versuche und Vorarbeiten, 2022)
Funerary rituals and mortuary cults are classics of religious studies research in ancient Egypt. Still, we know little about how the living interacted with ancestors and gods in daily life. The case study of the city of Memphis and its Saqqara necropolis in the late 2nd mil. BCE focusses on lived ancient religion, and demonstrates the spectrum of religious practices and options to configure religion and sociality through commemorative practices.